A Simple Three-Dimensional Matrix Method for Global Constellation Intrasatellite Link Topological Design. (30th March 2014) - Wang, Xiaoliang; Meng, Yansong; Su, Zhe; Wang, Gang; Zhang, Lixin; Gong, Deren
Abstract : A three-dimensional matrix method is proposed in this paper for Global Navigation Satellite System (GNSS) constellation Intrasatellite Link (ISL) topological design. The rows and columns of proposed matrix contain the information of both constellation orbit planes and satellites in each orbit plane. The third dimension of proposed matrix represents the time sequences during constellation movement. The proposed method has virtues of better advantage of conceptual clarity and computational efficiency, meanwhile, some properties of ISLs in the constellation can be proved easily. At the second part of this paper, a link assignment and optimal routing problem is proposed using three-dimensional topology matrixes, which aimed to minimize the relay hops during the process of data uploading to whole constellation network. Moreover, some practical constrains as antenna beam coverage and relative velocity are considered and analyzed in detail. Finally, some numerical simulations are provided, and the results demonstrated the promising performance of proposed topological method in reduction of computation burden, clear ISL conception, and so forth; the efficiency of provided optimal ISL routing problem is also proved.